Methodological Irregularities in Programming-Language Research. - Stefik, Andreas; Hanenberg, Stefan (Computer (00189162), 2017)
Substantial industry and government investments in software are at risk due to changes in the underlying programming languages, despite the fact that such changes have no empirically verified benefits. One way to address this problem is to establish rigorous evidence standards like those in medicine and other sciences.